A report about Zika virus in Brazil - Rosangela Cipriano; Carolina Cipriano Monteiro (Universidade de Santa Cruz do Sul, 2016)
Zika vírus, a Flavivirus first isolated in Africa, has spread to many countries around the world including Brazil. In this country, seven months after the football world cup, it was registered the occurrence of a epidemic, subsequently related to cases of microcephaly and Guillain-Barré syndrome. The virus is transmited via mosquito from Aedes genus, often following the bite from an infected vector. The febrile disease is self-limited, and there is no specific treatment. Few months after this outbreak in Brazil, the authorities recognized the relationship between the Zika vírus and the occurrence of Guillain Barré syndrome and microcephaly in newborns, correponding to fetal cerebral malformation or brain lesions. This finding is being a worldwide alert for strengthening the preventive measures, restricted to prevent insect bites and care for the environment.